Absolwenci szkół wyższych na zmieniającym się rynku pracy = University graduates on the changing labour market - Jelonek, Magdalena (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The main theme of the article refers to the consequences of dichotomization of situation concerning the graduates of popular and technical subject areas observed in the media discourse and in the statements of policy makers. The author considers the consequences of preserving these images and taking them for granted in the public discourse. In addition, she studies the effects they evoke in the students themselves, who under such an influence may decide on certain educational and professional strategies.
Keywords: absolwenci; szkolnictwo wyższe; rynek pracy; strategie edukacyjne; kompetencje zawodowe; university graduates; labour market; educational strategies; professional competencies